Why Eucalyptus Citriodora Potential as Biopesticide ? - Paramita Maris; Dwi Susilo Utami; Otto Marwoto; Nurbetti Tarigan (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Various efforts have been made to eliminate or at least reduce the negative impact of chemical pesticides that are currently widely used. One of these efforts is to use other effective control alternatives, such as bio-pesticides/botanical pesticides. Eucalyptus citriodora essential oil was previously better known in traditional medicine. However, many studies have shown that this essential oil has much potential to be used as a biopesticide. This article reviews the biopesticide potential of E. citriodora essential oil, including its herbicidal, bactericidal, fungicidal, nematicidal, insect-repellent, and insecticidal activities. E. citriodora oil contains citronellal, citronellol, 1,8-cineole, isopulegol, ?-pinene, and citronellyl acetate. Citronellal and citronellol are one of the main toxins in E. citriodora essential oil. However, this review shows that the oil has a broad spectrum of biological activity, making it a simple and environmentally friendly pesticide.